Characterization of Colletotrichum isolates causing Colletotrichum dieback of citrus in California - Camiletti, B. X.; Lichtemberg, P. S.; Paredes, J. A.; Carraro, T. A.; Velascos, J.; Michailides, T. J.
Dieback caused by Colletotrichum spp. is an emerging disease in California citrus groves. A large-scale survey with emphasis on seasonal variations of latent infections was conducted throughout citrus orchards in Fresno, Kern, and Tulare counties in 2019 and 2020. Latent infections on citrus leaves and twigs varied markedly between years. Isolates of Colletotrichum spp. were obtained from asymptomatic tissue, and two groups were formed based on colony and spore morphology. The morphological groups were further identified based on multigene sequence analysis using the DNA regions ITS1-5.8S-ITS2, TUB2, and GAPDH. Results revealed that isolates belong to two phylogenetic species, C. gloeosporioides and C. karstii, being C. karstii more frequently isolated. Representative isolates of each species were further selected and characterized based on the response of physiological variables to temperature. Both species had similar optimum growth temperatures but differed in maximum growth rates, with C. gloeosporioides exhibiting a greater growth rate than that of C. karstii on media. Pathogenicity tests on citrus trees demonstrated the ability of C. gloeosporioides and C. karstii to cause lesions on twigs and no differences in aggressiveness. A fungicide screening performed in this study determined that the DMI fungicides were the most effective in reducing the mycelial growth of C. gloeosporioides and C. karstii. The QoI fungicides showed a remarkably inhibitory impact on spore germination of both species. On average, C. karstii was more sensitive to the DMI fungicides than C. gloeosporioides. The findings of this study provide new information to understand the Colletotrichum dieback of citrus.
Keywords: ANTHRACNOSE; FUNGICIDE SENSITIVITY; MANDARIN; ORANGE; PATHOGENICITY; PHYLOGENETIC ANALYSIS; SURVEY